2020
DOI: 10.3390/ijerph17165914
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders among College Students in France: Characteristics, Help-and Care-Seeking

Abstract: The aim of this paper was to identify the characteristics of broader categories of eating disorders (ED) and help- and care-seeking among college students. An online cross-sectional study was conducted among students of the University of Rouen-Normandy, France. The Expali-validated algorithmic tool, combining SCOFF test (Sick, Control, One stone, Fat, Food) and body mass index, was used to screen eating disorders into three diagnostic categories: restrictive eating disorders, bulimic eating disorders, and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
3
27
2
Order By: Relevance
“…Another cross-sectional study with Pakistani medical students provided similar results by observing that 87.9% of high-risk participants were females ( 14 ). Also consistent with these findings were that obtained in France ( 21 ), the United States and Canada ( 26 ), Tunis ( 27 ), and Saudi Arabia ( 18 ), which all explored that female participants were more vulnerable to eating disorders risk than male participants. The National Comorbidity Survey Replication (NCS-R), a national community household survey of the prevalence and correlates of mental disorders in the United States, found that women have 1.75–3 times higher lifetime prevalence for anorexia, bulimia, or binge eating disorder than men ( 28 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Another cross-sectional study with Pakistani medical students provided similar results by observing that 87.9% of high-risk participants were females ( 14 ). Also consistent with these findings were that obtained in France ( 21 ), the United States and Canada ( 26 ), Tunis ( 27 ), and Saudi Arabia ( 18 ), which all explored that female participants were more vulnerable to eating disorders risk than male participants. The National Comorbidity Survey Replication (NCS-R), a national community household survey of the prevalence and correlates of mental disorders in the United States, found that women have 1.75–3 times higher lifetime prevalence for anorexia, bulimia, or binge eating disorder than men ( 28 ).…”
Section: Discussionsupporting
confidence: 81%
“…The current findings are in agreement with that reported in Pakistan among a sample of medical students where 23% appeared to have a high risk of eating disorders based on EAT-26 instrument ( 20 ). On the other hand, the prevalence of eating disorders among 1,493 college students of the University of Rouen-Normandy, France, exceeded our obtained one only slightly (24.8%) ( 21 ). In the United States of America, the prevalence of eating disorder risk among a sample of registered dietitian nutritionists was about 13%, which was less alarming than that obtained in the present study ( 22 ).…”
Section: Discussioncontrasting
confidence: 66%
“…Losing weight together with excessive levels of PA are characteristic for a subgroup of individuals with AN [2]. Since the SCOFF questionnaire itself does not allow for exact cross-sectional ED classification in adolescents at the moment, future research should perhaps focus on the development of a similar clinical algorithm as the recently developed Expali TM [45,46]. This can provide more comprehensive knowledge about prevalence rates of eating and other mental disorders, which is central to the provision of health care in the community [4].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1943 college students, with a mean age of 20.1 (±1.9) were evaluated. In the results, 63.4% were woman, 8.6% underweight, 12.4% overweight, and 4.6% obese, with a prevalence of EDs of 24.8%, especially in female students (31.6%) compared with males (17.0%) ( p < 0.001), being bulimic 13.3%, hyperphagic 8.6% and restrictive 2.9% [ 12 ]. In Ontario (Canada), they studied 301 students aged 17 to 20 years from Brock University during the first year of college and demonstrated that male and female students, and especially male, undergo changes in nutrition and body weight/composition, making their diet worse, increasing body weight, BMI, waist-to-hip ratio, and body fat, [ 10 ].…”
Section: Introductionmentioning
confidence: 99%